Case study: The Harbor Bridge in Bratislava. (13th October 2020) - Venglár, Michal; Sokol, Milan
Abstract: Bratislava Harbor Bridge is an important part of Slovak highway and railway network. The authorities of the bridge (Railways of the Slovak Republic and National Motorway Company) cannot afford to close it. In the case of closure, traffic in Bratislava would be paralyzed, as up to 100, 000 vehicles pass the bridge daily. Because of that, only dynamic tests during operation are possible, but the mentioned companies do not possess a sophisticated measurement system for structural health monitoring purposes. Therefore, a preliminary proposal of a measuring system has been prepared, in accordance with the fact that the bridge is one of the most complex structures in Slovakia. An initial and subsequent validated and verified FEM model have been used for numerical calculations. Time history analysis has also been used for verification and validation of the FEM model. This article also presents a comparison of current results of operational modal analysis and results of numerical analysis. It includes the recommendations for the fib Model Code 2020 (MC2020) as well.